A hybrid of the invasive plant Sphagneticola trilobata has similar competitive ability but different response to nitrogen deposition compared to parent. Issue 2 (12th February 2014) - Ni, Guangyan; Zhao, P.; Wu, W.; Lu, X.‐K.; Zhao, X.‐H.; Zhu, L.‐W.; Niu, J.‐F.
Abstract: Hybridization between introduced and related native species has been suggested to be a key driving force of evolutionary processes in invasions that may be accelerated by increasing nitrogen (N) deposition. We carried out two experiments to compare the competitive ability of a newly‐reported putative hybrid ( Sphagneticola calendulacea × Sphagneticola trilobata ) to that of its invasive paternal parent and investigate its response to different N additions. Growth of the hybrid increased by 39.62 ± 15.69 % when grown with the native parent but showed no significant changes when grown with the invasive parent. Growth of invasive S. trilobata showed no significant changes when grown with the other two taxa. The hybrid and invasive parent inhibited the growth of the native parent by 33.27 ± 15.26 % and 78.56 ± 3.13 %, respectively. Low level N addition (50 kg N ha −1 ) enhanced the growth of both the hybrid and native parent, whereas medium and high levels of N additions (150, 300 kg N ha −1 ) had no effects on hybrid growth but decreased native parent growth. However, all N treatments had no significant effects on the growth of the invasive parent. Our results suggest that the hybrid is an equal competitor to its invasive parent and is more susceptible to N deposition. Therefore, this hybrid could be a threat to native diversity but may decline more than the invasive parent under high N conditions.